Impacts of Demand Side Management Methods on the Feasibility of a Residential PV System - Mohammad Hasan Ghodusinejad; Sanaz Tabasi; Hossein Yousefi (Environmental Energy and Economic Research)
Energy consumption rising and fossil fuels drawbacks, which comprised of emissions and the concern of depletion, have forced nations to replace other sources such as the renewable energies to achieve a reasonable solution. Solar energy is one of the most promising resources to overcome the increasing demand in residential sector. In this regard, the PV systems are kind of conventional technologies which are widely integrated in buildings. However, the widespread utilization of these new resources, the feasibility analysis is needed to assess the economic profitability. This paper focus on the feasibility assessment of a residential PV system in the content of different electricity pricing schemes including flat pricing (S1), Time-of-Use pricing (S2) and Time-of-Use/tiered pricing (S3). Hence, the economic indicators (NPV and payback time) were calculated for the mentioned pricing models. The results showed that the S3 scheme has the highest NPV value (11258$) and the lowest payback period (3.8 years). In conclusion, the last two methods, known as Demand Side Management (DSM), are more beneficial compared to the flat pricing and proposed for the implementation of a PV system in Iran’s residential sector.